-26=6m+7m

Simple and best practice solution for -26=6m+7m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -26=6m+7m equation:


Simplifying
-26 = 6m + 7m

Combine like terms: 6m + 7m = 13m
-26 = 13m

Solving
-26 = 13m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-13m' to each side of the equation.
-26 + -13m = 13m + -13m

Combine like terms: 13m + -13m = 0
-26 + -13m = 0

Add '26' to each side of the equation.
-26 + 26 + -13m = 0 + 26

Combine like terms: -26 + 26 = 0
0 + -13m = 0 + 26
-13m = 0 + 26

Combine like terms: 0 + 26 = 26
-13m = 26

Divide each side by '-13'.
m = -2

Simplifying
m = -2

See similar equations:

| 1/3w-3/2=-4/5 | | x^2+12-8=0 | | 9x^2y+2y=2x | | -2/3x-7=4/3x-4/5 | | (a-4)/((3/a)-2) | | v/2-3v/4=v/8 | | -4/3x+1/5=-7/3x-7 | | 7x-11=5x-8 | | 6w+15=33 | | 8y-6=4y+1 | | x-14=33 | | 2x/3+2=12 | | y/5-4=y/3 | | 3(m+7)=18 | | 9y/8+2=11y/10 | | 10u^2-27u+5=0 | | 1-(2/x)-(3/x)=0 | | 10k-7=26-10k | | 128/14 | | (-11)+55+(-30)= | | 4.9+(-0.5)= | | 7x-12-3x=8x+-5 | | j/11=11 | | 4x+2x-3=2 | | 4x-8+2x=7+6x-14 | | c+(-8)+(-5)=0 | | 3-.166b=-3 | | 3-.16b=-3 | | 3-0.1666-b=-3 | | (3/a)+(5/6a)=4 | | (3x/4)-(1/2)=1 | | x-9=-9+x |

Equations solver categories